Growth in biofilms prepares Mycobacterium avium subsp. hominissuis for the macrophage microenvironment - McManus, William R.; Mulvey, Katie; Brooks, Elizabeth M.; Sanders, Sheri A.; Schorey, Jeffrey S. (Frontiers in Microbiology, 2025)
IntroductionMycobacterium avium subs. hominissuis is an opportunistic pathogen, causing pulmonary infections in individuals who are immunocompromised or whose respiratory systems are damaged due to injuries or diseases such as cystic fibrosis, bronchiectasis, or chronic obstructive pulmonary disease. M. avium is an environmental microbe commonly found in numerous natural and engineered habitats, including marginal niches where few species are able to survive. M. avium is able to persist in these habitats through biofilm formation, a process in which the hydrophobic mycobacterial cells preferentially adhere to a surface or to particles in suspension. The process of biofilm formation as well as the movement of M. avium from its environmental niche into a host entails a large shift in conditions and stressors. To mediate these transitions, it is necessary that M. avium responds by modulating its gene expression.MethodsWe used next generation sequencing to define changes in M. avium gene expression that occur during biofilm formation and during transition to survival inside host macrophages.ResultsWe identified genes that are differentially expressed in two different M. avium biofilm models relative to planktonic M. avium. We also identified genes that show differential expression in M. avium isolated from both infected macrophages and in biofilms when compared to planktonic M. avium. For some of these genes, we did not observe notable changes in expression in biofilm-grown M. avium pre- and post-infection, suggesting that genes expressed during residence in a biofilm may condition M. avium to survive in a macrophage.DiscussionOverall, these results identify a number of genes that may be important for biofilm formation and survival within macrophages and which will provide new foci for drug development that targets biofilm formation and M. avium virulence.